A narrative analysis of the justifications and excuses of serious employee fraud offenders - Andon, Paul; Free, Clinton (Contemporary Accounting Research, 2025)
Abstract Most fraud research in accounting has focused on controls rather than offenders' subjective experience, meaning that our understanding of motive in fraud (defined as linguistic devices employed to justify, interpret, or excuse actions) remains underexplored. This is particularly the case for employee fraud, which has been largely neglected relative to top management fraud or financial statement fraud. To provide a richer understanding of how fraud offenders make sense of their offending, we interviewed 30 serious employee fraud offenders to better investigate their typal vocabularies of motive. We focus on holistic narrative accounts to provide insights into the common justifications and excuses presented by employee fraud offenders. We develop a taxonomy of narrative constructions based on the explanatory locus of the accounts offered by offenders. We identify three common justifications, (1) inconsequentiality motives, (2) permission motives, and (3) unfair treatment motives, and three common excuses, (4) personal crisis motives, (5) addiction motives, and (6) appeasement motives. We draw implications for researching fraud, organizational control, and ethics in accounting education.